Designing Based on Evacuation Risk and Crowd-Disaster Management (Case Study: A Subway Station in Tehran) - et. al., Zahir Mottaki, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, individuals' lives in the community require communication with the environments outside the home and depend on presence in the community. In most urban communities, using public transportation is essential, meaning that public transportation sectors will witness a growing population every day. Crowd disaster and the collective panic shock are of the many human-made crises whose probability of incidence is higher after incidents like fire, earthquake, terrorist attacks, and so on. Tehran has one hundred and twenty-seven subway stations, each of which has been designed and built in a historic urban period and has generally failed in supplying the ideal space required given the financial, engineering, and urban pressures. In some stations, several stations intersect. By examining the studies conducted on crowd disaster and collective panic shock considering the roots and the factors exacerbating these phenomena, mentally and objectively, the study tried to find a way to evaluate the likelihood of crowd disaster in a subway station if an earthquake, threat Terrorist, gas leak, water intrusion or any obstruction occur in the rush hour at a busy subway station like Darvazeh Dowlat - which is the intersection of the two Tehran subway lines and one of the most significant nodes of human traffic in Tehran subway. In this study, using the stochastic differential equations (SDEs), the equation observing population behavior in a subway station was discovered and examined. Simulation was then done using MATLAB and the results showed that a crowd disaster is very likely to occur if anything happens to make all the people on a train leave through a busy station.